Fear of stigma from health professionals and family/neighbours and healthcare avoidance among PLHIV in Morocco: results from the Stigma Index survey Morocco - Rosemary M. Delabre; Amal Ben Moussa; Virginie Villes; Mohammed Elkhammas; Lahoucine Ouarsas; Daniela Castro Rojas Castro; Mehdi Karkouri (BMC Public Health, 2022)
Abstract Background Enacted or anticipated stigma among people living with HIV (PLHIV) can negatively impact healthcare engagement. We identified factors associated with having avoided HIV health services for fear of stigma among PLHIV in Morocco. Methods The Stigma Index survey was conducted in Morocco in March-June 2016. Factors associated with avoiding HIV testing and treatment services for fear of stigma by (A) health personnel or family/neighbours and (B) health personnel and family/neighbours compared to people who did not avoid health services for fear of stigma from either of the two sources were assessed using multinomial logistic regression models. Results Among 583 respondents, 280 (48.0%) were women and median number of years living with HIV was 5[IQR:2–7]. Half of the respondents reported avoiding health services for fear of stigma by health personnel and/or family/neighbours: (A) n = 228, 39.1% and (B) n = 68, 11.7%. After adjustment on perceived health status, not having had easy access to antiretroviral treatment ((A) aRR [95% CI] = 1.76[1.16; 2.68]; (B) 2.18[1.11; 4.27]), discrimination by PLHIV ((A) 1.87[1.12; 3.13]; (B) 3.35[1.63; 6.88]) and exclusion from social activities ((A) 1.70[1.10; 2.61]; (B) 2.63[1.39; 5.00]) were associated with having avoided health services for fear of stigma by health personnel or/and family/neighbours. Being female (2.85[1.48; 5.47]), not having been referred for an HIV test for suspected symptoms 3.47[1.67; 7.22], having discussed sexual/reproductive health with a health professional (4.56[2.38; 8.71]), and not having the feeling to influence decisions on local projects for PLHIV (3.47[1.37; 7.83], were associated with having avoided health services for fear of stigma by both sources. Conclusion Results suggest a cumulative effect of fear of stigma and discrimination among PLHIV in Morocco. PLHIV who have experienced discrimination may seek to avoid similar situations at the expense of their health. These results should inform multi-level interventions and broader advocacy efforts to reduce stigma and discrimination.